Características de la práctica pedagógica en el área de Química - Blanchar-Añez, Francisco Javier (Revista Científica, 2020)
This article is derived from the research carried out in the official Educational Institution Center of Popular Integration (IPC), of the Tourist District of Riohacha, Colombia, whose main objective was to analyze the scientific competences developed in the students through the characteristics of institutional pedagogical practice in the area of chemistry; aspects contemplated around the theoretical guidelines (pedagogical and didactic) established in the Colombian Educational System by competences. Given the integral character of the research developed, which included the analysis of the official curriculum of the educational establishment, the identification of the properties of the pedagogical practices in the classroom and the evaluation process in the area of chemistry, different methodological techniques were implemented; such as the documentary analysis for the first and the third aspect and the observation and descriptive record for the second. The investigation was framed in the quantitative approach following a design of descriptive type, working with the units of analysis of 34 documentary elements, 4 teachers and 523 students of the central headquarters of the official institution. The results showed that this educational institution has a generic official curriculum based on the traditional conception of teaching, and its classroom practices in the area of chemistry are characterized by the master's exposition of the teacher around the declarative contents; besides the absence of stimulating activities of complex and challenging cognitive processes for the students around procedural and attitudinal aspects.